The Darkening: The Darkening # 1 ([Place of publication not identified] : Clarion Books, 2022)
In this thrilling and epic YA fantasy debut the only hope for a city trapped in the eye of a cursed storm lies with the daughter of failed revolutionaries and a prince terrified of his throne. .
new ya book 2022 summer.
Keywords: Demographic Orientation; sex and gender; Family life; marriage and divorce; Women